2015
DOI: 10.1371/journal.pone.0138213
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Gene-Expression Signatures and Protein Markers for Breast Cancer Grading and Staging

Abstract: The grade of a cancer is a measure of the cancer's malignancy level, and the stage of a cancer refers to the size and the extent that the cancer has spread. Here we present a computational method for prediction of gene signatures and blood/urine protein markers for breast cancer grades and stages based on RNA-seq data, which are retrieved from the TCGA breast cancer dataset and cover 111 pairs of disease and matching adjacent noncancerous tissues with pathologists-assigned stages and grades. By applying a diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…However, its role in vivo , the regulation of genes or cellular function, have still to be discerned. PCDHA8 is also involved in WNT pathway and has been suggested as a potential marker for the prediction of BC classification and staging of since it was part of a set of genes identified in a computational analysis of tissue‐based gene expression data to identify possible gene signatures and markers of blood or urine proteins . We found this gene expressed in CTCs isolated from TNBC patient's blood samples, however, little is known about its involvement in tumor development or metastasis.…”
Section: Discussionmentioning
confidence: 90%
“…However, its role in vivo , the regulation of genes or cellular function, have still to be discerned. PCDHA8 is also involved in WNT pathway and has been suggested as a potential marker for the prediction of BC classification and staging of since it was part of a set of genes identified in a computational analysis of tissue‐based gene expression data to identify possible gene signatures and markers of blood or urine proteins . We found this gene expressed in CTCs isolated from TNBC patient's blood samples, however, little is known about its involvement in tumor development or metastasis.…”
Section: Discussionmentioning
confidence: 90%
“…Serum SELDI-TOF-MS protein profiling is a powerful method used for biomarker discovery and can be used to distinguish patients with BC from NCI with high sensitivity and specificity (18). It has previously been reported that monitoring protein-based markers in blood and urine samples may be used for cancer staging (19). In the past decade, a number of studies have utilized SELDI-TOF to identify proteomic patterns in biological fluids, including serum, urine and nipple aspirates (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…The association between the somatic mutation and the gene expression profile is directly linked with the health of the cancer patients and are highly important factors that decide their grade and overall survival. Various studies have predicted the grade and survival of the cancer patients by scrutinizing the somatic alteration and expression profiles of cancer-specific significant genes (An, Yang, Cheng, Wang, & Zhang, 2015;Mercatelli, Ray, & Giorgi, 2019;Yao, Zhang, Du, Liu, & Xu, 2015). The accurate and robust prediction of grade and survival are essential for better prognostic and selection of treatment strategies especially for the cancer with high incidence and low survival rate, such as gliomas.…”
Section: Introductionmentioning
confidence: 99%